Educação para a Sustentabilidade: Uma visão da história da educação socioambiental no Brasil e o caso da REDECRIAR de Porto Alegre RS - Martos, Doroty Aparecida (2012)
The present master thesis aims at to research theory and action of Sustainability Education (in the scopes of the formal and not formal education), presenting a historical view and a case study. The main objective is to reflect on aspects of the existing relations between socio-environmental NGOs, in one hand, and public schools, in the other, and its respective impact in the localities where they are being implemented, as well as, in the individuals engaged in them. It is intended to analyze these relations, considering the diverse strategies used in the studied processes, the applied methodologies of action, and to reflect on public politics that support those actions.